PELAKSANAAN FUNGSI KEPEMIMPINAN KETUA HIMPUNAN MAHASISWA JURUSAN PADA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI PADANG - BUSPAMI ARIFIN (Jurnal Bahana Manajemen Pendidikan, 2018)
This research is aimed to describe the implementation of the functions of the organization’s leadership in science education faculty student padang state university. Total of population is 237 people. Taking the sample using full sampling tecniques. Instrument student used a questionnire using likert scale. Data is processed using the formula average (mean) based on the result of the research obtained revealed the implementation of the result of the organization’s leaqdership student 3,98 are in good category Keyword : functions leadership, organization’s